La Zone critique - Jérôme Gaillardet; Soraya Boudia (Revue d'anthropologie des connaissances)
This interview goes back over the emergence of the concept of “critical zone,” which refers to the thin layer between the subsoil and the lower atmosphere where life on earth is concentrated, and the construction of a new research infrastructure – Critical Zone Observatories (OZCAR) – in the context of reconfigurations in Earth and Environmental Sciences and in the face of climate change and the ecological crisis. The interview reviews efforts to develop an infrastructure for overcoming points of ignorance and incomplete knowledge about complex interactions between gas and the atmosphere, stone, water, and the living.